Inward FDI and economic growth nexus: A case of emerging Brazil from Latin America - Farrukh Nawaz Kayani; Omar Mahmoud Al-Ammary; Misbah Sadiq (Scientific Papers of the University of Pardubice, Series D: Faculty of Economics and Administration, 2021)
Capital stock is possessing pivotal importance in stimulating the economic growth and development of any country. Inward FDI is considered as one of the important catalysts of economic development particularly for the resource and capital poor countries. In this article we have examined the relationship between inward FDI and economic growth in case of one of the emerging economies of Latin America i.e., Brazil. We took annual time series data for the dependent and independent variables like inward FDI, per capita Gross Domestic Product (GDP), employment, capital formation, and exports for the period ranging from 1996 to 2019. Initially, we applied Pearson Correlation test for examining the issue of Multicollinearity. Then we ran Ordinary Least Square Regression and Random Effect Regression Analysis for gauging the nature of relationship between the variables as well as for testing the robustness of the results. We found that FDI has a positive and significant relationship with GDP and the exports. Whereas, FDI has insignificant relationship with the employment and capital formation. The article holds an important policy implication for the other developing countries of Latin America; they need to attract good amount of inward FDI to achieve the robust economic growth and development.
Keywords: F21; F23; F43; 330; Brazil; Inward FDI; Economic Growth; Exports; Employment; Capital Formation; Latin America